2006
DOI: 10.1007/s11056-006-9021-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation of seed mass and its effects on germination in Polylepis australis: implications for seed collection

Abstract: South American Polylepis mountain forests are recognised as being one of the most endangered forest ecosystems in the world. Reforestation measures have been strongly recommended but may be hampered due to the very low seed germination reported for several Polylepis species. In order to facilitate reforestation we analysed the influence of seed mass on germination probability for Polylepis australis seeds in the Co ´rdoba mountains (central Argentina). We collected seeds from 43 trees distributed throughout fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
4
23
1
8
Order By: Relevance
“…Seeds of four (2700 m a.s.l.) to five individual trees (all other altitudes) were randomly selected and weighed individually to the nearest 0.1 mg. As the results of a former study (Seltmann et al ., 2007) revealed that lighter P. australis seeds often lack embryos, seeds were divided evenly into two seed mass classes: light and heavy seeds. Replicates of three Petri dishes, each containing 30 -35 seeds, were taken from these two fractions.…”
Section: Sampling and Experimental Designsupporting
confidence: 67%
See 1 more Smart Citation
“…Seeds of four (2700 m a.s.l.) to five individual trees (all other altitudes) were randomly selected and weighed individually to the nearest 0.1 mg. As the results of a former study (Seltmann et al ., 2007) revealed that lighter P. australis seeds often lack embryos, seeds were divided evenly into two seed mass classes: light and heavy seeds. Replicates of three Petri dishes, each containing 30 -35 seeds, were taken from these two fractions.…”
Section: Sampling and Experimental Designsupporting
confidence: 67%
“…Germination of P. australis seeds was tested in a climate chamber with a warm white light source at temperatures of 20 ° C/10 ° C (12 h of light/12 h of darkness), which are known to reflect optimum temperatures (Seltmann et al ., 2007). Seeds were laid on filter paper and kept moist with deionized water for 50 days, after which time the germination rate reached zero.…”
Section: Sampling and Experimental Designmentioning
confidence: 99%
“…1). Even though seed weight was previously addressed to be important for a successful germination (Kidson and Westoby 2000;Seltmann et al 2007;Van Mo¨lken et al 2005), its importance for Fallopia japonica s.l. has to be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Research in Andean ecosystems has shown that plants may have limited recruitment due to the production of nonviable seed (Enrico et al 2004). The lack of viability of the seed has been related to water stress, constant frost, and a lack of nutrients such as nitrogen (Enrico et al 2004;Kessler 2006), which all lead to the production of sterile seeds (Renison et al 2004;Seltmann et al 2007). This is a possible explanation for the fact that we recorded only 3 individual Polylepis in the germination trial, which would not be enough to support a restoration project using soil redeployment as the main method.…”
Section: Discussionmentioning
confidence: 99%